2021
DOI: 10.1177/1356766721993861
|View full text |Cite
|
Sign up to set email alerts
|

Understanding tourists’ motivations to launch a boycott on social media: A case study of the #BoycottMurree campaign in Pakistan

Abstract: This research paper studies the domestic tourism destination boycott of Murree, the most popular tourist spot in Pakistan. Murree, a hill spot in the footsteps of the Himalayan mountain ranges, attracts millions of tourists from all over Pakistan every year due to its natural scenery and easy accessibility. However, weak regulation and unmanageable demand have made the local hospitality industry quixotic, prompting affiliated businesses in Murree to exploit tourists. Subsequently, the #BoycottMurree campaign w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 88 publications
(106 reference statements)
0
7
0
Order By: Relevance
“…One very interesting aspect is that boycotting and discursive activities seem closely connected (Delistavrou et al, 2017). This direction implies that social media might be very useful in promoting boycott campaigns, as recent studies indicate (Yousaf et al, 2021). Social media are clearly a channel for activism due to the wider access and increased visibility activists are able to gain (Uldam, 2018).…”
Section: Discussionmentioning
confidence: 98%
“…One very interesting aspect is that boycotting and discursive activities seem closely connected (Delistavrou et al, 2017). This direction implies that social media might be very useful in promoting boycott campaigns, as recent studies indicate (Yousaf et al, 2021). Social media are clearly a channel for activism due to the wider access and increased visibility activists are able to gain (Uldam, 2018).…”
Section: Discussionmentioning
confidence: 98%
“…Traditionally, tourism and travel-related activities and affiliated industries have performed below par in Pakistan because of the broader socio-economic repercussions of Pakistan's alignment with the war against terror since 2001 (Yousaf, 2017). However, with amelioration in law and order situations and the up-gradation of infrastructural facilities and road networks, there is an upsurge in inbound tourism and increased demand for domestic tourism in Pakistan (Yousaf et al , 2021). In recent years, popular international food vloggers visited Pakistan and highlighted the culinary uniqueness of different regions in the country.…”
Section: Introductionmentioning
confidence: 99%
“…Significantly, boycotters strive to get the media's attention in order to harm the reputation of a specific business, destination or a country (Hawkins, 2010;Yousaf et al, 2021). The growth of social media has only enhanced this capacity (Gretzel, 2017;Seyfi et al, 2021).…”
Section: Boycotts In Tourismmentioning
confidence: 99%
“…The growth of social media has only enhanced this capacity (Gretzel, 2017;Seyfi et al, 2021). For instance, the study of Yousaf et al (2021) on the #BoycottMurree campaign showed how campaign momentum on social media affected Murree which is a popular tourist destination in Pakistan. This is also especially evident in the case of Boycott, Divestment and Sanctions (BDS) campaigners pushing for a boycott of Israel's hosting of the Eurovision Song Contest 2019 and accusing Israel of exploiting the artistic event to whitewash its human rights violations against Palestinians (Morrison, 2022;Shepherd, 2021).…”
Section: Boycotts In Tourismmentioning
confidence: 99%